2023
DOI: 10.1021/acs.jpcc.3c00187
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Uniform Facets on the Thermodynamics of Ligand Exchanges on Colloidal Quantum Dots

Abstract: Nanocrystal surfaces play a critical role in dictating their physical and chemical properties. Colloidal semiconductor nanocrystals, or quantum dots, are generally synthesized with insulating aliphatic ligands, but these ligands can be post-synthetically exchanged with other molecular species for a variety of applications. While previous work has investigated the thermodynamics of ligand exchanges on quasi-spherical quantum dots through sensitive isothermal titration calorimetry and 1 H NMR measurements, the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 57 publications
0
4
0
Order By: Relevance
“…Besides, the exchanges of natural cadmium carboxylate (Cd(RCOOH) 2 ) with zinc chloride (ZnCl 2 ) on CdSe tetrahedra (111) and CdSe cubes (100) were investigated (Figure 9B). 90 From these measurements, unexpected results showed that the thermodynamics of ligand exchange between these surfaces were almost identical. In our group, ITC was used to obtain the thermodynamic parameters of EDA adsorbing onto the surface of QDs.…”
Section: ■ Thermodynamics Of Ligand Exchangementioning
confidence: 91%
See 3 more Smart Citations
“…Besides, the exchanges of natural cadmium carboxylate (Cd(RCOOH) 2 ) with zinc chloride (ZnCl 2 ) on CdSe tetrahedra (111) and CdSe cubes (100) were investigated (Figure 9B). 90 From these measurements, unexpected results showed that the thermodynamics of ligand exchange between these surfaces were almost identical. In our group, ITC was used to obtain the thermodynamic parameters of EDA adsorbing onto the surface of QDs.…”
Section: ■ Thermodynamics Of Ligand Exchangementioning
confidence: 91%
“…However, these indirect methods for studying thermodynamics have their limitations. With the well-known surface of QDs and the establishment of ligand exchange models, ITC, a direct method for monitoring thermal change, is increasingly used to study the thermodynamics of ligand exchange. , Thus, a more in-depth characterization of the ligand exchange can be conducted to reflect the most authentic ligand exchange. In addition to the coordination between the head groups of organic ligands and the surface of QDs, there is a weak noncovalent interaction between the tail groups of ligands.…”
Section: Thermodynamics Of Ligand Exchangementioning
confidence: 99%
See 2 more Smart Citations